One-Pot Deconstruction and Conversion of Lignocellulose Into Reducing Sugars by Pyridinium-Based Ionic Liquid–Metal Salt System - Naz, Sadia; Uroos, Maliha; Asim, Azmat Mehmood; Muhammad, Nawshad; Shah, Faiz Ullah (Frontiers in Chemistry, 2020)
Constantly decreasing fossil resources and exceeding energy demands are the most alarming concerns now-a-days. The only way out is to develop efficient, safe and economic biomass processing protocols that can lead towards biofuels and fine chemicals. This research is one of such consequences involving the deconstruction and conversion of wheat straw carbohydrate constituents into reducing sugars via one-pot reaction promoted by Lewis acidic pyridinium based ionic liquids (PyILs) mixed with different metal salts (MCl). Various parameters such as the type of metal salt, loading amount of metal salt, time, temperature, particle size of biomass and water content which affect the deconstruction of wheat straw have been evaluated and optimized. Among the studied IL and metal salt systems, the best results were obtained with [BMPy]+CoCl3‒. The dinitrosalicylic acid (DNS) assay was used to determine the percentage of total reducing sugars (TRS) generated during treatment of wheat straw. The deconstructed wheat straw was characterized with various analytical tools i.e. FTIR, SEM and XRD analyses. The ionic liquid‒metal salt system was recycled for subsequent treatment of wheat straw. Statistical parameters were calculated from analysis of variance (ANOVA) at 0.05 level of confidence.